2014
DOI: 10.1017/s175173111400113x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of konjac flour inclusion in gestation diets on the nutrient digestibility, lactation feed intake and reproductive performance of sows

Abstract: This study was conducted to investigate the effects of konjac flour (KF) inclusion in gestation diets of sows on nutrients digestibility, lactation feed intake, reproductive performance of sows and preweaning performance of piglets. Two isoenergetic and isonitrogenous gestation diets were formulated: a control diet and a 2.1% KF-supplemented diet (KF diet). Both diets had the same NDF and insoluble fiber (ISF) levels, but the KF diet had higher soluble fiber (SF) level. The day after breeding, 96 multiparous s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
19
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 32 publications
2
19
1
Order By: Relevance
“…This was in line with our previous study in that the inclusion of 2.1% KF in the gestation diet of sows did not increase the diet viscosity [46]. …”
Section: Discussionsupporting
confidence: 93%
“…This was in line with our previous study in that the inclusion of 2.1% KF in the gestation diet of sows did not increase the diet viscosity [46]. …”
Section: Discussionsupporting
confidence: 93%
“…Konjac flour (KF) is a water soluble, viscous dietary fiber with a high water-binding capacity (15.5 mL H 2 O/g) [13,14]. KF mainly contains konjac glucomannan (KGM), which is composed of β-1,4-linked d -mannosyl and d -glucosyl residues at a molar ratio of 1.6:1.0 as the main chain with a small number of branches through β-1,3 mannosyl units [15].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the transition from pregnancy to lactation is characterized by physiological and metabolic changes, such as a progressive decrease in insulin sensitivity during late gestation and lactation (5,6), which may unfortunately result in decreased lactation feed intake of sows (7,8). Our previous studies showed that sows provided with konjac flour (KF) during gestation significantly increased their voluntary feed intake during lactation and demonstrated improved litter weight at weaning (9)(10)(11), probably as a result of insulin sensitivity improvement. However, the mechanism by which dietary KF exerts the benefit is poorly understood.…”
mentioning
confidence: 99%